Central nervous system histoplasmosis: Multicenter retrospective study on clinical features, diagnostic approach and outcome of treatment. Issue 13 (March 2018) - Wheat, Joseph; Myint, Thein; Guo, Ying; Kemmer, Phebe; Hage, Chadi; Terry, Colin; Azar, Marwan M.; Riddell, James; Ender, Peter; Chen, Sharon; Shehab, Kareem; Cleveland, Kerry; et al.
Abstract : Abstract: Central nervous system (CNS) involvement occurs in 5 to 10% of individuals with disseminated histoplasmosis. Most experience has been derived from small single center case series, or case report literature reviews. Therefore, a larger study of central nervous system (CNS) histoplasmosis is needed in order to guide the approach to diagnosis, and treatment. A convenience sample of 77 patients with histoplasmosis infection of the CNS was evaluated. Data was collected that focused on recognition of infection, diagnostic techniques, and outcomes of treatment. Twenty nine percent of patients were not immunosuppressed. Histoplasma antigen, or anti- Histoplasma antibodies were detected in the cerebrospinal fluid (CSF) in 75% of patients. One year survival was 75% among patients treated initially with amphotericin B, and was highest with liposomal, or deoxycholate formulations. Mortality was higher in immunocompromised patients, and patients 54 years of age, or older. Six percent of patients relapsed, all of whom had the acquired immunodeficiency syndrome (AIDS), and were poorly adherent with treatment. While CNS histoplasmosis occurred most often in immunocompromised individuals, a significant proportion of patients were previously, healthy. The diagnosis can be established by antigen, and antibody testing of the CSF, and serum, and antigen testing of the urine in most patients. Treatment with liposomal amphotericin B (AMB-L) for at least 1 month; followed by itraconazole for at least 1 year, results in survival among the majority of individuals. Patients should be followed for relapse for at least 1 year, after stopping therapy. Abstract : Supplemental Digital Content is available in the text